Violence - perception - video games: new directions in game research : young academics at the clash of realities 2017-2018 - Alvarez Igarzábal, Federico; Debus, Michael S.; Maughan, Curtis L. (Studies of digital media culture, 2019)
"This volume compiles papers from the Young Academics Workshop at the Clash of Realities conferences of 2017 and 2018. The 2017 workshop - Perceiving Video Games - explored the video game medium by focusing on perception and meaning-making processes. The 2018 workshop - Reframing the Violence and Video Games Debate - transcended misleading claims that link video games and violent behavior by offering a range of fresh topical perspectives. From BA students to postdoctoral researchers, the young academics of this anthology stem from a spectrum of backgrounds, including game studies, game design, and phenomenology."--Back cover